Analyzing Students’ Experimental Design Skills: Insights from a Rasch Model Study - Yudi Kurniawan; Andi Suhandi; Achmad Samsudin; Muslim Muslim (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2026)
This study aimed to investigate first-year university students’ experimental design skills in regional context of at a private teacher training institution (LPTK) in Singkawang, West Kalimantan. Utilizing a survey design, data were collected from 112 participants with diverse genders and secondary education backgrounds (Science, Vocational, and Social Sciences). The assessment utilized four targeted items from the Scientific Inquiry Literacy (ScInqLit) instrument developed by Wenning, translated and contextualized into the Indonesian context. Data were evaluated using Rasch model analysis to examine both overall competence levels and potential demographic bias through Differential Item Functioning (DIF). The results indicated that the students’ ability in designing experiments was remarkably low, as evidenced by a mean person measure of -1.15 logits, which falls substantially below the item difficulty baseline (0.0 logit). Furthermore, the DIF analysis revealed that all item probabilities exceeded 0.05, demonstrating that the instrument was free from gender and academic background biases. This neutrality implies that the low competence in designing experiments is a widespread issue across all student demographics. These findings emphasize an urgent need for LPTKs to redesign foundational science curricula, shifting from conventional “cookbook” laboratory tasks to explicit inquiry-based interventions to foster robust experimental design skill.